Measurement of Tangible and Intangible Impacts of Telecentres on Rural Communities - Ghazala, Tabassum; Yeo, Alvin Wee (Association for Computing Machinery, 2015)
The issue of evaluating the Information and Communications Technologies (ICTs) intangible impacts remains to be unresolved, especially when it comes to evaluating the impacts of ICTs on non-user beneficiaries. The telecentres have been established to disseminate knowledge from basic to advanced level, stimulating the socio-economic status of the underprivileged communities. After a thorough review of the literature, it is found that researchers paid much more attention towards evaluating traditional measurable impacts of telecentre (from both users and non-users perspectives) such as income, health, education. Albeit very few studies have identified non-measureable intangible impacts on users such as psychological wellbeing and empowerment, non-measureable intangible impact particularly from the non-users perspectives have largely been neglected. Telecentre has been existing for almost more than two decades, now the question is, are the non-measurable impacts important? Hence, we believe an alternative qualitative research methodology (The Most Significant Change) will help to evaluate the intangible impacts of ICTs perceived by its non-users such as (self-esteem, self-confidence, feelings of happiness and pride). These stories-based approach can produce diverse, unexpected and emergent impacts from the community’s social perspectives, which might not be catered for by using other orthodox research approaches based on success related pre-stated indicators.